Tumor angiogenesis and anti-angiogenic therapy - Ziheng Guo; Xu Jing; Xiaoting Sun; Shishuo Sun; Yunlong Yang; Yihai Cao; Jing Ni; Xuehong Zhang (Chinese Medical Journal, 2024)
Abstract. Anti-angiogenic drugs (AADs), which mainly target the vascular endothelial growth factor-A signaling pathway, have become a therapeutic option for cancer patients for two decades. During this period, tremendous clinical experience of anti-angiogenic therapy has been acquired, new AADs have been developed, and the clinical indications for AAD treatment of various cancers have been expanded using monotherapy and combination therapy. However, improvements in the therapeutic outcomes of clinically available AADs and the development of more effective next-generation AADs are still urgently required. This review aims to provide historical and perspective views on tumor angiogenesis to allow readers to gain mechanistic insights and learn new therapeutic development. We revisit the history of concept initiation and AAD discovery, and summarize the up-to-date clinical translation of anti-angiogenic cancer therapy in this field.